PENGARUH PEMBERIAN PENYULUHAN PENDIDIKAN SEKS TERHADAP SIKAP SEKSUALITAS REMAJA USIA 17-19 TAHUNDI SMA NEGERI 3 KABUPATEN PROBOLINGGO PADA TAHUN 2014 - Fandik Fathur Rohman; Ahmad Rifa’i; Anin Wijayanti (STIKES Insan Cendekia Medika Jombang, 2014)
Adolescent sexual attitudes today many leads to deviant behavior, sex education often considered taboo toformal school, information about sexuality is important for teens, through counseling information can betransformed to adolescent sexuality. The purpose of this study was to analyze the effect of sex education onthe attitudes of sexuality education in adolescents aged 17-19 years in SMA 3 Probolinggo.This study used a pre-experimental design of one-group pre-post test design. Samples of the research weremostly adolescents aged 17-19 years in SMA 3 Probolinggo regency number of 72 respondents were takenusing simple random sampling technique. The samples were given a questionnaire pre-test followed by theprovision of sex education counseling and post-test questionnaire was given. Independent variablesmeasured were sex education counseling on sexuality and the dependent variable measured was the attitudeof sexuality in adolescents aged 17-19 years.Based on the analysis using the Wilcoxon match pairs test using SPSS version 16, the error rate of 0.05, thevalue of ρ = 0.000 is obtained, which means that ρ <α then H1 is accepted, which means there is the effect ofgiving sex education on sexuality attitudes in adolescents aged 17 -19 years.In this study it can be concluded that there is effect of sex education on the attitudes of sexuality inadolescents aged 17-19 years in SMA 3 Probolinggo.Suggested that the results of this study can be served as the foundation for the school which the educationprograms for youth in order to improve the knowledge, attitudes and even sexual behavior as expected canbe implementated.Keywords : Sex education, Teen Attitudes, Adolescents